Research trends and hotspots in the mental health of widowed older adults: a bibliometric analysis - Lin, Doudou; Wu, Jiaojiao; Chen, Weibing; Shen, Xiangying; Cai, Zhongxiang; Wang, Nian; Fu, Dou; Li, Yinglin; Ma, Xiaojie (Frontiers in Psychiatry, 2025)
BackgroundThe mental health of widowed older adults has garnered increasing research attention due to its profound impact on well-being and quality of life. Despite growing scholarly interest, a comprehensive bibliometric analysis of evolving research trends, key topics, and knowledge structures remains scarce. This study aims to identify key research themes, emerging trends, and interdisciplinary linkages to inform future studies on the mental health of widowed older adults.MethodsA bibliometric analysis was conducted using data from the Web of Science Core Collection (2004–2024). CiteSpace, VOSviewer, and the R package “Bibliometrix” were utilized to visualize publication trends, country and author collaborations, keyword co-occurrences, theme analysis, and emerging research topics.ResultsA total of 891 articles were analyzed. The United States produced the highest number of publications, followed by China and the United Kingdom, with the United States, England, and Canada exhibiting strong research collaborations. Depression, prevalence and mental health were identified as core research themes, while life satisfaction and social support emerged as growing areas of interest. Citation burst and thematic evolution analyses revealed shifting scholarly interest from clinical and diagnostic concerns towards psychosocial adaptation and person-centered approaches over time.ConclusionThis bibliometric study systematically maps the research landscape, hotspots, and emerging trends in the mental health of widowed older adults over the past two decades. The findings provide valuable insights for researchers seeking to identify key research directions, foster interdisciplinary collaborations, and develop targeted interventions to support the mental well-being of widowed older adults.